82.6k views
4 votes
Y 7 • y 9

Multiply or divide as indicated.

1 Answer

3 votes

For this case we have the following expression:


y^ 7 * y^ 9 =

By definition of multiplication of powers of the same base, we have to put the same base and add the exponents, that is:


a ^ n * a ^ m = a ^ {n + m}

So:


y ^ 7 * y ^ 9 = y ^(7 + 9) = y ^ {16}

Answer:


y^(16)

User Kumar D
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.